Bullying, cyberbullying, and empathy as longitudinal predictors of self-esteem - Benítez -Sillero, Juan de Dios; Falla, Daniel; Córdoba-Alcaide, Francisco; Zych, Izabela (Psychology, Society & Education, 2024)
Research has shown that high self-esteem has numerous personal and social benefits, especially in adolescents. However, it is necessary to examine whether involvement, as aggressors or victims, in online and offline aggressive behaviours or the presence or absence of empathy, affective and cognitive, can influence adolescents’ self-esteem. The present study analysed whether bullying, cyberbullying, and empathy were longitudinally related to self-esteem. It was hypothesized that low bullying and cyberbullying involvement and high affective and cognitive empathy would be related to high self-esteem. The sample consisted of 876 students (48.7% girls) aged 12-19 years (M = 14.91, SD = 1.71) through a longitudinal study with two waves of survey data collection. Low bullying victimization and high cognitive empathy were found to be related to high self-esteem cross-sectionally and longitudinally. Likewise, lower affective empathy, low cyberbullying victimization, and low bullying aggression were longitudinally related to higher self-esteem. It is suggested that decreased bullying and cyberbullying and increased cognitive empathy could have numerous benefits for self-esteem improvement in prevention and mental health intervention programs with adolescents who are in the educational stage.